The Influence of Principal Leadership, Discipline and Motivation on the Performance of Private Mts Teachers In Banyuasin Regency - Khasanah, Esti Nur; Ismail, Gunawan; Moelyati, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research aims to describe the influence of school principal leadership, discipline and motivation on the performance of private MTs teachers in Banyuasin Regency in detail. The data testing method for measuring the variables in this research uses Multiple Linear Regression Analysis. Associative research type. The total respondents were 154 teachers from 20 private MTs in Banyuasin Regency. The research results show that: (1) Leadership, discipline and motivation simultaneously influence the performance of private MTs teachers in Banyuasin Regency. (2) In particular, leadership, discipline and motivation have a positive effect on the performance of private MTs teachers in Banyuasin Regency.